Recent developments in the control of anaplasmosis, babesiosis and cowdriosis. Proceedings of a workshop - Dolan, T.T. (International Laboratory for Research on Animal Diseases, 1992)
This workshop proceeding discusses the importance of anaplasmosis, babesiosis and cowdriosis; the methods of control being used for the diseases and the problems encountered with these control methods; recent findings in the epidemiology and molecular biology of these diseases, and developments towards new vaccines. Topics of discussion include distribution, economic importance, control measures, diagnosis, approaches to new vaccines, and in vitro cultivation. Under the topic diagnosis, papers are presented on development of diagnostic reagents for anaplasmosis and babesiosis; serodiagnosis of Cowdria ruminantium, and DNA probes for this species. The papers under approaches to new vaccines examine molecular biology of rickettsiae with particular reference to gene organization and structure in Anaplasma marginale and Cowdria ruminantium; methodological approaches to the study of resistance in cowdriosis and the possible role of cell-mediated immunity; progress in development of subunit vaccines for anaplasmosis, development of an antigenically defined vaccine against Babesia bigemina; vaccination against Babesia bovis using antigens produced by recombinant DNA technology, and identification of Babesia divergens protective antigens. The last topic, in vitro cultivation, discusses cultivation of babesia, progress with the cultivation of Cowdria ruminantium in endothelial cells, and in vitro cultivation of Anaplasma marginale.